1994
DOI: 10.1136/jnnp.57.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of neocortical cerebral blood flow deficits in dementia of the Alzheimer type: a [99mTc]-d,l-HMPAO SPECT study.

Abstract: Regional cerebral blood flow (rCBF) was measured with high resolution brain dedicated single photon emission computer tomography (SPECT) and [SS-Tc]-d,lI-hexamethyl-propylene-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 41 publications
(10 reference statements)
2
57
0
1
Order By: Relevance
“…In addition, concerning the absence of correlation with the dorsolateral prefrontal cortex, a possible interpretation might be that AD patients focus mainly on the storage of information to the detriment of processing function. This predominance of storage function could be a consequence of the reduction of working-memory resources (Baddeley, 1986), or of the presence of a disconnection between anterior and posterior parietal areas (Morris, 1994a(Morris, , 1994b, or even of a focal prefrontal dysfunction (Waldemar et al, 1994). Further studies will be necessary to investigate more precisely these interpretations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, concerning the absence of correlation with the dorsolateral prefrontal cortex, a possible interpretation might be that AD patients focus mainly on the storage of information to the detriment of processing function. This predominance of storage function could be a consequence of the reduction of working-memory resources (Baddeley, 1986), or of the presence of a disconnection between anterior and posterior parietal areas (Morris, 1994a(Morris, , 1994b, or even of a focal prefrontal dysfunction (Waldemar et al, 1994). Further studies will be necessary to investigate more precisely these interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…The first one refers to a frontal lobe pathology. Indeed, some studies have shown that frontal lobe degeneration is relatively often associated with AD (Waldemar et al, 1994). However, some authors (D'Esposito & Grossman, 1996;Fuster, 1993 ;Weinberger, 1993) have proposed that executive control would require the integration of information coming from different cerebral areas.…”
Section: Discussionmentioning
confidence: 99%
“…Verbal function. This included two tests, which may also be considered as tests of semantic memory: Familiar Faces [Waldemar et al 1994] with naming of 28 generally wellknown faces; and Boston Naming Test with 60 objects in line drawings.…”
Section: Neuropsychological Testsmentioning
confidence: 99%
“…Reduced cerebral perfusion and decreased metabolism in white matter and cerebral cortex were reported to occur predominantly in the temporal, parietal, and frontal areas. [3][4][5] Recent observations showed that reduced cerebral blood flow is rather global in AD, without significant variation between different brain regions. 5 Reduction in metabolic activity was also observed in several other cortical areas, such as the posterior cingulate gyrus and occipital cortex.…”
mentioning
confidence: 99%
“…[3][4][5] Recent observations showed that reduced cerebral blood flow is rather global in AD, without significant variation between different brain regions. 5 Reduction in metabolic activity was also observed in several other cortical areas, such as the posterior cingulate gyrus and occipital cortex. 6,7 Cerebral hypoperfusion, progressive and diffuse cortical atrophy, and leukoaraiosis were all correlated with cognitive decline.…”
mentioning
confidence: 99%